Hukum Pembebasan Masyarakat Timur Dekat Kuno : Misharum, Andurarum, Hammurabi, dan Yobel - Nepho Gerson Laoly (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract The law of liberation of slaves already existed in ancient Near Eastern societies. Using qualitative methods, the researcher conducted a study of the literature to enter into the laws of the peoples of the Ancient Near East. The law of deliverance was owned by the Akkadians (andurarum), the Babylonians (the misharum and hammurabi law), and the Israelites (jubilee law). The use of the word דְּר֛וֹר (liberation) indicates the similarity of concepts between the nations of the Ancient Near East. The word דְּר֛וֹר also provides evidence regarding the dating of the time of enactment of this law around 2000 B.C. Although there are similarities, but Leviticus 25 gives the law of the Jubilee superior to other laws in ancient Near Eastern societies. Abstrak Hukum pembebasan para budak sudah ada di masyarakat Timur Dekat Kuno. Menggunakan metode kualitatif, peneliti melakukan studi literatur untuk masuk ke dalam hukum-hukum masyarakat di Timur Dekat Kuno. Hukum pembebasan telah dimiliki oleh bangsa Akkadian (andurarum), bangsa Babel (misharum dan hukum Hammurabi), serta bangsa Israel (hukum Yobel). Penggunaan kata דְּר֛וֹר (pembebasan) menunjukkan kesamaan konsep antara bangsa-bangsa di Timur Dekat Kuno. Kata דְּר֛וֹר juga memberikan bukti mengenai penanggalan waktu pemberlakukan hukum ini sekitar tahun 2000 S.M. Kendati ada kesamaan, tetapi Imamat 25 memberikan hukum Yobel yang lebih unggul dari hukum lainnya di masyarakat Timur Dekat Kuno.